Water Quality Assessment of Paper Mills Effluent Discharge Areas - Zaman Shakil, Md. Shakilur; Mostafa, M. G. (Al-Nahrain Journal of Science, 2021)
The study attempted to assess the water quality around paper mill effluents discharge areas. Several physicochemical parameters and the Canadian Council of Ministers of the Environment (CCME) Water Quality Index (WQI) were considered to determine the pollution level of surface and groundwater in the selected paper mills areas located in Saidpur, Gobindaganj, and Dupchanchia Upazilas of Bangladesh. Physicochemical characterization of the surface water around the paper mills areas showed that the concentration of EC, TSS, BOD5, COD, phenols, NO3–N, and K+ were exceeded the surface water standard, whereas the DO level ranged from 1.63 to 3.5 were found below the Environmental Conservation Rules (ECR), 1997 standard. Besides, the BOD, COD, and Mn ion concentrations of groundwater exceeded the drinking water standard. In most sampling sites, the WQI of the surface water showed ‘marginal’ category, and the groundwater quality showed ’fair’ category. The study observed that the toxic effluents discharged from the paper mills caused harm to the aquatic ecosystem.